A photo‐responsive F‐box protein FOF2 regulates floral initiation by promoting FLC expression in Arabidopsis. (13th July 2017) - He, Reqing; Li, Xinmei; Zhong, Ming; Yan, Jindong; Ji, Ronghuan; Li, Xu; Wang, Qin; Wu, Dan; Sun, Mengsi; Tang, Dongying; Lin, Jianzhong; Li, Hongyu; et al.
Summary: Floral initiation is regulated by various genetic pathways in response to light, temperature, hormones and developmental status; however, the molecular mechanisms underlying the interactions between different genetic pathways are not fully understood. Here, we show that the photoresponsive gene FOF2 ( F‐box of flowering 2 ) negatively regulates flowering. FOF2 encodes a putative F‐box protein that interacts specifically with ASK14, and its overexpression results in later flowering under both long‐day and short‐day photoperiods. Conversely, transgenic plants expressing the F‐box domain deletion mutant of FOF2 (FOF2ΔF), or double loss of function mutant of FOF2 and FOL1 ( FOF2‐LIKE 1 ) present early flowering phenotypes. The late flowering phenotype of the FOF2 overexpression lines is suppressed by the flc‐3 loss‐of‐function mutation. Furthermore, FOF2 mRNA expression is regulated by autonomous pathway gene FCA, and the repressive effect of FOF2 in flowering can be overcome by vernalization. Interestingly, FOF2 expression is regulated by light. The protein level of FOF2 accumulates in response to light, whereas it is degraded under dark conditions via the 26S proteasome pathway. Our findings suggest a possible mechanistic link between light conditions and the autonomous floral promotion pathway in Arabidopsis. Significance Statement: Plant floral initiation is regulated by different flowering pathway in response to multiple environmental factors, but it is not clear how different pathways interact to control flowering. This study demonstrates a possible mechanistic link between light conditions and autonomous flowering pathway. We identified a F‐box protein FOF2, which is regulated by light and autonomous pathway, and controls flowering‐time by promoting FLC expression.